Effectiveness of livelihood projects in reducing gender based violence: case of Nyanga district, ward 27, Manicaland province - Made, Chiedza Diana (Midlands State University, 2017)
This study is an investigation into the effectiveness of livelihood projects as a strategy in reducing Gender Based Violence (GBV). The study explored and highlighted the major causes of GBV, the livelihood options for women, the relationship between GBV and livelihoods and the extent to which livelihood projects as a strategy have reduced GBV and empowered women using the case study on Nyanga, Ward 27. The major causes of GBV are poverty, lack of economic independence among women, patriarchal norms and values and unequal representation of women in decision making processes. The study noted a negative and positive relationship between GBV and livelihoods was noted. GBV impacts negatively on women’s livelihoods in that it leads to failure of projects hence negative livelihood outcomes. A positive relationship was noted in that, with livelihood projects women have increased income which they use to access food, education and health services and other material things necessary for survival. The study employed mixed research methodologies and data was collected through in-depth/one-on-one interview, focus group discussions and key informant interviews. Data analysis was guided by Sara Longwe’s Women Empowerment Framework and the DFID Sustainable Livelihood Framework. The study also discovered that financial, human, physical, natural and social assets/resources are required to sustain the women’s livelihoods in Nyanga. The women in Nyanga are being negatively affected by the economic, political and technological context in which they are living. Natural disasters such as drought and diseases are also affecting women’s livelihoods negatively. The study also noted that traditional and religious practices have a negative impact on women’s livelihoods in the district. Livelihood projects as a strategy have reduced GBV and empowered women socially and economically. Women engaged in livelihoods projects have managed to achieve eight of the nine sustainable livelihood outcomes which are economic security; nutrition security; food security; health security; education security; community participation; access to institutions and gender. Therefore, there is need to embark women to start livelihood projects. While those already in such process intensify their efforts in order to get maximum returns.